An artificial pancreas for automated blood glucose control in patients with Type 1 diabetes. (May 2015) - Schmidt, Signe; Boiroux, Dimitri; Ranjan, Ajenthen; Jørgensen, John Bagterp; Madsen, Henrik; Nørgaard, Kirsten
Automated glucose control in patients with Type 1 diabetes is much-coveted by patients, relatives and healthcare professionals. It is the expectation that a system for automated control, also know as an artificial pancreas, will improve glucose control, reduce the risk of diabetes complications and markedly improve patient quality of life. An artificial pancreas consists of portable devices for glucose sensing and insulin delivery which are controlled by an algorithm residing on a computer. The technology is still under development and currently no artificial pancreas is commercially available. This review gives an introduction to recent progress, challenges and future prospects within the field of artificial pancreas research.